Machine learning-guided fabrication of NiO/CoO and CuO/CoO based nanocomposites for high-performance supercapacitors - Hussain, Aqsa; Almalki, Abdulraheem SA; Sami, Abdul; Tariq, Muhammad; Zafar, Farhan; Khan, Muhammad Ali; Akhtar, Naeem; Ahmad, Sagheer; Rehman, Muhammad Usman Ur; Mersal, Gaber A.M.; Ibrahim, Mohamed M. (Materials chemistry and physics, 2026)
Different transition metal oxides (TMOs) have been extensively reported for supercapacitor applications. However, they often struggle with stability and specific charge. To overcome these limitations, bimetallic composite materials have been widely developed, leveraging synergistic effects to improve catalytic efficiency. However, optimizing these systems remains a significant challenge due to the incomplete understanding of the individual contributions of each component to the overall electrocatalytic performance. This aspect has received limited attention to date. To address this, we used machine learning (ML) algorithms during the synthesis strategy. In this study, we have fabricated NiO/CoO and CuO/CoO based nanocomposites via a hydrothermal approach. ML optimized NiO/CoO based nanocomposite has shown high specific charge (511C g−1) as compared to CuO/CoO (415C g−1) at a current density of 1.5 A g−1. This high specific charge of NiO/CoO can be attributed to the synergistic effect of Ni and Co, petal-like morphology providing highly exposed electroactive sites leading to efficient ion or electron transport. The NiO/CoO electrode also demonstrated excellent cycling reversibility and stability alongside a high-power density of 3028 W kg−1 and energy density of 75 Wh kg−1 calculated from a two-electrode system. These findings highlight the potential of integrating ML into material design workflows to address the challenges in optimizing bimetallic TMOs, advancing their application as promising electrode materials for next-generation supercapacitors. •Petal like NiO/CoO nanocomposite was prepared by facile hydrothermal method.•NiO/CoO nanocomposite had a specific capacitance of 387 Fg-1 at 1.5 Ag-1 current density.•Synergistic behavior of NiO and CoO enhance its electrochemical efficiency making it suitable for supercapacitor application.